2007
DOI: 10.1080/02646830701691343
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the relationship between mother–infant interaction and maternal cognitive function in mothers with mental illness

Abstract: There is evidence for a deleterious effect of maternal mental illness on motherinfant interaction. Presence of mental illness and lowered maternal cognitive function independently predict quality of interaction, but their combined effect on interaction is unclear. A pilot study was conducted to explore the relationship between maternal serious mental illness (SMI), cognitive function, and mother-infant interaction. Six mothers with SMI (two with schizophrenia and four with depression) and 12 mothers with no ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…Similarly Kemppinen, Kumpulainen, Moilanen and Ebeling (2006) found that 75% of mothers who were identified as being "at risk" in lack of sensitivity towards their infant 6 to 8 weeks postpartum, also reported depressive symptoms. Evidence shows that depressed mothers are less sensitive towards their babies (Murray et al, 1996;Steadman et al, 2007), being more intrusive or withdrawn (Black et al, 2007;Field, Hernandez-Reif & Diego, 2006;Herrera, Reissland & Shephard, 2004;) and less accurate in interpreting their baby's emotions (Broth, Goodman, Hall & Raynor, 2004). Similarly paternal depression has been associated with a less optimal father -infant relationship (Field, Hossain & Malphurs, 1999;Field, 2010; for a review, see Wilson & Durbin, 2010) with examples of less involvement with their child (Roggman, Boyce, Cook & Cook, 2002).…”
Section: Parental Mental Health and Parent-infant Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly Kemppinen, Kumpulainen, Moilanen and Ebeling (2006) found that 75% of mothers who were identified as being "at risk" in lack of sensitivity towards their infant 6 to 8 weeks postpartum, also reported depressive symptoms. Evidence shows that depressed mothers are less sensitive towards their babies (Murray et al, 1996;Steadman et al, 2007), being more intrusive or withdrawn (Black et al, 2007;Field, Hernandez-Reif & Diego, 2006;Herrera, Reissland & Shephard, 2004;) and less accurate in interpreting their baby's emotions (Broth, Goodman, Hall & Raynor, 2004). Similarly paternal depression has been associated with a less optimal father -infant relationship (Field, Hossain & Malphurs, 1999;Field, 2010; for a review, see Wilson & Durbin, 2010) with examples of less involvement with their child (Roggman, Boyce, Cook & Cook, 2002).…”
Section: Parental Mental Health and Parent-infant Interactionsmentioning
confidence: 99%
“…The quality of the early dyadic interaction between the primary caregiver and baby is important for the child's socio-emotional, cognitive, language and brain development (Hay & Pawlby, 2003;Murray, FioriCowley, Hooper & Cooper, 1996;Trevarthen & Aitken, 2001), for the formation of secure attachment (Steadman et al, 2007;Crittenden, 1995;Tomlinson, Cooper & Murray, 2005) and the child's future mental health (Skovgaard et al, 2008). A failure to establish a satisfactory early parent-baby relationship may also put the baby at risk of child abuse and neglect (Scannapieco & Connell-Carrick, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Goodman & Brumley, 1990;Riordan et al 1999;Hipwell et al 2000;Albertsson-Karlgren et al 2001;Steadman et al 2007;Wan et al 2007), although it is not always clear whether the effect of gender was examined in these papers. This has not been reported in other studies focusing on mother-infant interaction within a mental health sample (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The CARE‐Index has a high degree of stability and has been validated with families of different ethnic backgrounds (Crittenden & Bonvillian, ). The CARE‐Index has been used in numerous studies with a wide variety of maternal samples, including deaf mothers, mothers with mental retardation, abusive mothers, neglectful mothers (DiLalla & Crittenden, ), adolescent mothers (Ward & Carlson, ), low‐income mothers (Fuertes, Faria, Soares, & Crittenden, ), and mothers with psychiatric disorders (Leadbeater, Bishop, & Raver, ; Leventhal, Jacobsen, Miller, & Quintana, ; Mullick, Miller, & Jacobsen, ; Steadman et al., ). The CARE‐Index also has been utilized with high‐risk children such as premature infants (Forcada‐Guex, Pierrehumbert, Borghini, Moessinger, & Muller‐Nix, ), infants with failure to thrive (Crittenden, ; Ward, Kessler, & Altman, ), and maltreated infants (Crittenden & DiLalla, ).…”
Section: Assessment Tools Related To Attachmentmentioning
confidence: 99%